Criminal Liability for Perpetrators of Human Trafficking against Children as Victims - Dukey, Indriyani (jurnal.unprimdn.ac.id, 2025)
Human trafficking is one of the major crimes involving human rights violations. The main problem today is the crime of human trafficking, which is why almost every country is trying to reduce it because the number continues to increase from year to year. As in the example discussed in this paper, 28% of TIP victims are children, according to data collected from the journal. This study examines the sentencing of the court panel against TIP perpetrators who use children as unpaid sex workers. Literature review is an important legal material for Normative Juridical legal research in this study. The results of the study indicate that the perpetrator has legally committed TPPO against the child victim so that she can work as a prostitute without a warrant, and the perpetrator has also fulfilled the provisions of the Law on the Crime of Human Trafficking. Therefore, the panel of judges sentenced her to 5 years in prison and a fine of 120,000,000 Million Rupiah which will be replaced with 2 months in prison if the fine is not paid.